2011
DOI: 10.1088/0957-4484/22/48/485706
|View full text |Cite
|
Sign up to set email alerts
|

First-order metal–insulator transition and infrared identification of shape-controlled magnetite nanocrystals

Abstract: The first-order metal-insulator transition (MIT) in magnetite has been known for a long time but is still controversial in its nature. In this study, well-defined magnetite nanocrystals (NCs) with controllable size, shape and terminated surface are first employed to elucidate this important issue, and new discoveries such as a highly suppressed phase transition temperature are identified by monitoring the variable-temperature electric resistance and infrared spectroscopy. Significantly, by carefully comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…The small bump observed in the FC branch at the same temperature supports this interpretation. The shift of the Verwey transition to lower temperatures has been already reported in Fe 3 O 4 NPs with sizes smaller than ≈15 nm, and attributed to size 34 or shape 35 effects. The origin of the second bump at T 1 ≈ 45 K is not clear and might be related to thermal relaxation/unblocking processes of the smallest Fe 3 O 4 (<10 nm) cores observed in TEM images, which is consistent also with the increase of the FC curves at low temperatures due to weak inter-particle interactions of small particles.
Figure 2( a ) DC magnetization curves obtained in zero-field-cooled (ZFC, lower branch) and field-cooled (H FC = 2.39 kA/m, upper branch) modes for PEI-Fe 3 O 4 (filled black circles) and Au@PEI-Fe 3 O 4 (open red circles) NPs.
…”
Section: Resultssupporting
confidence: 66%
“…The small bump observed in the FC branch at the same temperature supports this interpretation. The shift of the Verwey transition to lower temperatures has been already reported in Fe 3 O 4 NPs with sizes smaller than ≈15 nm, and attributed to size 34 or shape 35 effects. The origin of the second bump at T 1 ≈ 45 K is not clear and might be related to thermal relaxation/unblocking processes of the smallest Fe 3 O 4 (<10 nm) cores observed in TEM images, which is consistent also with the increase of the FC curves at low temperatures due to weak inter-particle interactions of small particles.
Figure 2( a ) DC magnetization curves obtained in zero-field-cooled (ZFC, lower branch) and field-cooled (H FC = 2.39 kA/m, upper branch) modes for PEI-Fe 3 O 4 (filled black circles) and Au@PEI-Fe 3 O 4 (open red circles) NPs.
…”
Section: Resultssupporting
confidence: 66%
“…Such a phenomenon is related to the grafting process and the formation of binary blends between PANI and LIG, due to the successful interaction of lignin with the conductive polyaniline through their hydroxyl and carbonyl groups. However, the MAPLE processed PANI-LIG coating presents similar infrared maxima as in the case of DC specimen, the identified absorption peaks being in good accordance with the results described in the literature for PANI-based materials [55,56].…”
Section: Resultssupporting
confidence: 87%
“…However, the traditional variable‐temperature XRD, differential scanning calorimetry (DSC), and resistance measurements for identification of the insulator‐to‐metal transition (IMT) accompanied with SPT are only performed on the bulk sample 27. Fortunately, the far‐IR spectroscopy with the advantage of excluding the influence of the grain boundaries provides sensitive spectral response to the intrinsic lattice vibrations during the phase transition of finite‐sized nanomaterials 28. 29 As shown in Figure 4, we found that, for both of the nanosheet and the bulk, the IR transmittance shows strong steplike peaks (ca.…”
mentioning
confidence: 99%